Low threshold incoherent random lasing with spectral overlap optimization of size-tuned plasmonic nanorods - Gayathri, R. (2021)
Plasmonic random lasers continue to generate significant interest in the fields of optics and photonics due to their improved performance. This owes to the greater scattering strength and enhanced local field offered by the plasmonic scatterers. However, absorption losses and fluorescence quenching are the major setbacks to plasmonic random lasers. Design of plasmonic random lasers with low threshold and enhanced emission intensity continues to be a challenging area of research. This paper demonstrates that the use of one-dimensional anisotropic plasmonic structures can help to overcome these limitations to a great extent by manipulating the spectral overlap between the scatterers and gain medium. A low threshold random lasing system has been experimentally realized in this context, using Ag nanorods with aspect ratio tuned to give optimal scattering and field enhancement. The optimal aspect ratios were deduced using FDTD simulations and incoherent random lasing was experimentally demonstrated at a low threshold of 116 µJ/cm or 0.023 MW/cm . We also demonstrate through spatial coherence measurements that the bright emission from the plasmonic random laser enables speckle contrast reduction upto 0.034 with single pulse illumination.